Representation of Social Inequality in the Film 12th Fail (2023) - Cut Cahayana Putri; Sidiq Setyawan (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − Social inequality refers to conditions of inequality of access, opportunity and utilization of resources between community groups. This phenomenon can be seen in differences in income, quality of education, infrastructure development, and legal treatment. That issue is also a structural issue in India, a country that still faces sharp inequalities between social classes, rural and urban areas, and powerful groups and marginalized communities. Film media has a strategic role as a means of representing social reality, because it is able to convey critical messages visually and narratively. The Indian biographical film “12th Fail” by Vidhu Vinod Chopra has become an object of study because it tells the story of the struggle of the character Manoj from a poor family in facing an unequal social system. Method − Descriptive qualitative research methods are applied through Roland Barthes' semiotics approach, including denotation, connotation and myth analysis. Primary data are sourced from scenes and film dialogue, while secondary data are from relevant scientific literature. Findings − The results showed four main forms of social inequality, including inequalities in quality and educational facilities, socioeconomic status inequalities, rural and municipal infrastructure inequalities and legal justice inequalities. The representation shows how social systems tend to favour the powerful and limit the social mobility of the poor.